Comparative toothbrush abrasion resistance and surface analysis of different dental restorative materials. (November 2022) - Pinto, P.; Carvalho, A.; Silva, F.S.; Gomes, J.R.; Carvalho, O.; Madeira, S.
Abstract: Different materials have been used for dental restorations, and, like a natural tooth, they are subject to wear due to abrasion produced by toothbrushing during oral hygiene routine. The purpose of the present study was to evaluate the toothbrush abrasion resistance of four restorative dental CAD/CAM materials available on the market: an acrylic polymer - PMMA (DD TempMED HI, Dental Direkt), a composite resin (BRILLIANT CRIOS cerec HT A1 14, Coltene, CH) and two ceramics (polychromatic feldspathic porcelain (VITABLOCS RealLife 1M1C, Vita Zahnfabrik) and 3Y-TZP zirconia (DD Bio ZW iso color, Dental Direkt), under the same conditions. The specimens were immersed in a mixture of toothpaste and deionized water and subjected to simulated toothbrushing tests following ISO/TR14569–1:2007. Tests were performed under 3.5 N load, 5 Hz frequency, and 10 mm stroke length. The toothbrush abrasion resistance of each tested material was evaluated through the specific wear rate. The surface roughness and color difference were assessed for all materials before and after 16 years of simulated toothbrushing tests. Statistical analysis was performed by applying one-way ANOVA. The results revealed that the surface characteristics of restorative dental materials were modified by the toothbrushing, except for zirconia. The polymer was the material more susceptible to toothbrushing wear, presenting the highest surface roughness, specific wear rate, and surface change. On the other hand, zirconia showed to be about 10 times more resistant to abrasion than feldspathic porcelain and composite and about 100 times more resistant than polymer. Thus, it is a promising solution for the promotion of longevity restorations. Graphical Abstract: ga1 Highlights: The aim of this study was to evaluate the toothbrush abrasion resistance of 4 commercial restorative dental materials under the same conditions. The toothbrush abrasion resistance of each tested material was evaluated through the specific wear rate; Color differences and lightness caused by toothbrushing were verified. However, the obtained values are below the perceptibility threshold The polymer was the most affected by toothbrushing, the one with the greatest color change and highest lightness. Zirconia is about 10 times more resistant to abrasion than feldspathic porcelain and composite and about 100 times more resistant than polymer.